DIFFERENCES IN INTELLECTUAL FUNCTIONING BETWEEN GIRLS AT YOUNGER SCHOOL AGE - Boris Popović; Dejan Madić; Dušanka Tumin; Tatjana Jezdimirović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Proper selection of means of physical exercising included in development gymnastics result in children's correct growth and development, improvement of general motor status of organism, as well as positive effect on cognitive abilities (at younger age) and conative characteristics, which was confirmed by a number of earlier research works. The sample of girls consisted of 305 girls aged 7-11 that were not engaged in organized physical activities, as well as 300 girls engaged in the program of development gymnastics. According to decimal years, the girls were divided into four age groups within range of one calendar year. The test Raven's Progressive Matrices in Color was applied for assessment of intellectual functioning with an aim to determine intellectual abilities of the two groups of girls. Results of chisquare test indicated statistically significant differences between the two groups of subjects in age groups of 8-9 and 9-10 applying a more relaxed criterion of statistical conclusion (p=0.05). Analyzing the distribution of female subjects within three intellectual groups (below-average, average, and above-average), a lower number of girls included in the program of development gymnastics was observed in the category of below-average intellectual abilities, especially in the two oldest groups. In addition, in most age groups, a higher number of girls with average and above-average intellectual abilities were observed among those engaged in the program of development gymnastics. According to the results of this research, authors concluded that successful practice of development gymnastics requires at least average intellectual abilities of younger school girls.